Another kind of war: the nature and history of terrorism - Lynn, John A. (Yale University Press, 2019)
In the years since 9/11, there has been a massive surge in interest surrounding the study of terrorism. This volume applies distinguished military historian John Lynn’s lifetime of research and teaching experience to this difficult topic. As a form of violence that implies the threat of future violence, terrorism breeds insecurity, vulnerability, and a desire for retribution that has far-reaching consequences. Lynn distinguishes between the paralyzing effect of fear and the potentially dangerous and chaotic effects of moral outrage and righteous retaliation guiding counterterrorism efforts. In this accessible and comprehensive text, Lynn traces the evolution of terrorism over time, exposing its constants and contrasts. In doing so, he contextualizes this violence and argues that a knowledge of the history and nature of terrorism can temper its psychological effects, and can help us more accurately and carefully assess threats as well as develop informed and measured responses.